Abdominal pain: when should we consider acute appendicitis? : epidemiological and clinical characteristics of children admitted to the Uruguayan Police Forces hospital between june 2008 and november 2014 (Archives of Pediatrics of Uruguay, 2020)
Introduction: acute abdominal pain is a reason for frequent consultation in Pediatrics. It is important to diagnose acute appendicitis in time, thus reducing morbidity and mortality.Objective: to analyze the epidemiological characteristics, statistics and evolution of children admitted for abdominal pain. Identify the clinical and paraclinical characteristics that lead to diagnosis of acute appendicitis.Methodology: observational, descriptive, retrospective study of children under 14 years of age previously admitted to the Pediatric ward from June 2008 to November 2014. Data source: Review of Electronic Medical Records.Results: we included 217 patients, 52% girls (112) and 48% boys (105). The pain was in the right iliac fossa 51% (110). 29% (63) of the cases took place in Spring, 24% (52) Summer, 24% (52) Autumn and 23% (50) in Winter. Of the children with appendicitis: 61% (54) presented vomiting, 26% (23) saburral tongue, 40% (39) fever, and 53% of them (19) had 38 to 38.9°C temperature. 45% (40) of them showed more than 15,000 leukocytes, 41% (37) less than 15,000 and no blood count was performed on 14% of patients. CRP was lower than 20 mg/L in 32% (28) of patients and higher in 22% (20) of them. Abdominal ultrasound was normal in 56% (22) of patients. 5% (6) of them presented complications during hospitalization.Conclusions: the most frequent diagnosis was acute appendicitis, followed by nonspecific abdominal pain. Most appendicitis cases diagnosed were confirmed intraoperatively and through pathological anatomical analysis. Pain as a symptom had a better diagnostic performance. Vomiting and fever are associated with a higher probability of acute appendicitis. 40% of the patients had fever, mainly between 38 and 38.9°C. Leukocytosis and C-reactive protein were leading factors for the diagnosis of appendicitis. Abdominal ultrasound was also inconclusive.
Keywords: Appendicitis; Abdominal pain